Representation of Adèle’s Sexual Behaviorin ‘Blue Is The Warmest Color’ - Nadira Azzahra; Triyono Lukmantoro, S.Sos, M.Si (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Film as one of mass media is capable to distribute ideological messages toward audience. Therefore, film is often utilized in constructing sexuality and lesbianism issues. ‘Blue Is The Warmest Color’ produced by French Cinema presents sexuality issues which related to lesbian sexual behavior in a slightly different viewpoint from previous productions, as Adèle’s image stands for. This study aims to find lesbian values domination depicted by the representation of Adèle inBlue Is The Warmest Color’. This study uses descriptive qualitative method, along with ‘The Codes of Television’ analysis technique found by John Fiske. The theories used for this study consist of Representation in Film, Sexual Behavior, and Sex in Lesbian Culture. The analysis shows number of results, those are: 1) Based on constructionist approach, facial expression shot functions as ‘sign’ which interpretated according particular sexuality concepts, resulting ‘the mean. 2) Lesbian values domination can be seen trough the body of Adele which disassociate from heteronormativity concept, the mutual pleasure with Emma, the sexual behavior freedom in public means the freedom of heterosexual ritual. 3) Adele’sexual behavior shows her sexual fluidity. 4) Sexual behavior nowadays is not always related to sex and gender binarity